The effect of different sintering temperature to the properties of cow bone hydroxyapatite - Shahrizal Md Hussein (School of Materials Engineering, 2012)
This research aims to extract HA from natural sources that is cow bone since it has plenty of resources, high potential as raw materials, low cost of production, simple processing and similar structure to human bone. In addition, this research will use extraction method that biological safe to produce HA from cow bone.